Produksi Enzim Selulase Dan Xilanase Dari Eupenicillium Javanicum Dengan Substrat Bonggol Nanas Menggunakan Solid-State Fermentation - Emmilia Dannisa Pratiwi; Evelyn Evelyn; Said Zul Amraini (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Bioprocess is a biotechnology science that utilizes microorganisms to produce a biochemical product, one of which is an enzyme that can function as a catalyst. Enzyme requirements continue to increase along with the growth of the bioprocess industry. Cellulase and xylanase are enzyme products commonly used in industry, such as pulp and paper, detergents, food, textiles, and others. Pineapple tuber waste contains cellulose and hemicellulose which have potential as pure substrates such as cellulose and xylan. The process of enzyme formation can be done by the fermentation process. This study aims to determine the effect of temperature (25, 30 and 35 ° C) and pH (4, 6 and 8) on the production of cellulase and xylanase enzymes in a state of solid fermentation (solid state fermentation) and compare the activity of its enzymes under submerged fermentation. fermentation). The fermentation process was carried out for 96 hours with tempeature conditions and pH. Enzyme activity was measured using UV-Vis spectrophotometry with the DNS method seen at a wavelength of 540 nm. The highest enzyme activity was obtained at a temperature of 35 ˚C and pH 6 of 0.262 U / mL for cellulase enzymes and 1.683 U / mL for xylanase enzymes. Keywords: Celullase, Enzyme, Solid-state fermentation, Submerged fermentation, Xylanase